Psychometric Properties of a Polish Version of the Parental Stress Index III (PSI III) - Pisula, Ewa; Barańczuk, Urszula (Journal of developmental and physical disabilities, 2020)
The Parenting Stress Index (PSI) has been translated into multiple languages. The aim of the present study was to develop a Polish version of the PSI III. A total sample size of 678 parents (308 parents of children with ASD, 59 parents of children with Down syndrome, 65 parents of deaf children, 34 parents of children with other developmental disorders, and 212 parents without developmental disabilities) participated in the study. The Polish version of the PSI III was characterized by: (1) good internal consistency, (2) a three-factor structure, including Parent domain, Child domain, and the children’s and parents’ difficulties in adapting to the external demands resulting from the children’s developmental disorder, and (3) negative correlations between parental stress and parental well-being. Implications for the research and clinical practice are discussed.